THE IMPOSSIBILITY OF CHANGE IN THE STATE OF INNOCENCE PROVIDED FOR IN ART. 5th, LVII, OF THE FEDERAL CONSTITUTION (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
The present work aims to study the main aspects of the impossibility of changing the state of innocence provided for in the Federal Constitution, considering that of all the constitutional principles, the principle of the presumption of innocence, of article 5, item LVII, of the Constitution is one of the most important, as it protects the freedom of the individual. Given the constitutional provision, the subject should be considered innocent, and the State is responsible for proving his guilt. It is concluded that the proposed theme is relevant, considering that it is subject to controversies before the provision of the provisional execution of the penalty before the final judgment of the criminal sentence, which affronts the application of the constitutional principle and infra constitutional rules. During the research, books, periodicals, articles, and everything else that could be found to enrich the work were used.